Temperature and anisotropy effects in the application of the hindered diffusion model to composite laminates. (July 2019) - Rodriguez, Luis A; Damley-Strnad, Alexandra; Grace, Landon R
The one-dimensional hindered diffusion model was applied to gravimetric moisture uptake data for a six-ply high-temperature quartz-fiber-reinforced bismaleimide laminate. Diffusion behavior was evaluated as a function of specimen geometry and temperature to determine the effect on both diffusivity and the binding and unbinding probabilities of diffusing water molecules predicted by the model. Pre-equilibrium experimental uptake data were used to recover model parameters, including equilibrium moisture content, for specimens designed with intentionally-low planar surface-to-edge area ratios of 20, 12.5, and 5. Gravimetric uptake data for fully-immersed laminates at 25°C, 37°C, and 50°C was used to determine diffusion parameters and characterize the temperature and geometry-dependent behavior of the laminate. A parameter recovery method employing least-squares regression was used to determine best-fit parameters of the hindered diffusion model, including diffusivity ( DZ ), equilibrium moisture content (M ∞ ), and molecular binding (γ ) and unbinding (β ) probabilities. Results indicate that binding and unbinding probabilities are independent of specimen geometry and material anisotropy. Further, while molecular binding and unbinding probabilities were both directly correlated with immersion temperature, the hindrance coefficient was modestly lower at 50°C, indicating increased bound-phase molecules at high temperatures.